A Note on the Global Existence for the Strong Solution of the Stochastic Three-Dimensional Axially Symmetric Euler Equations (Journal of Mathematical Study, 2025)
This paper establishes the global existence of the pathwise solutions for thestochastic 3-D incompressible Euler equations with the axially symmetric initial dataand axially symmetric additive noise.